Applying HF and VHF/UHF partial discharge detection for distribution transformer - Maneerot, Sakda; Kando, Masaaki; Pattanadech, Norasage (My University, 2019)
This paper represents application of high frequency (HF) and very high frequency/ultrahigh frequency (VHF/UHF) partial discharge (PD) detection for a distribution transformer. A capacitive sensor is used to detect the HF electric field caused by charge transfer inside oil–paper insulation due to PD at the defect site, and an electromagnetic sensor or antenna is used for detecting electromagnetic PD transients in the air outside the investigated transformer in the near-field region. Three types of artificial PD sources in air and insulating liquid, which are corona discharge, surface discharge and air void discharge in pressboard, were investigated. Three identical distribution transformers were rated at 22 kV, 400 V and 50 kVA, and were designed and constructed. The first transformer was filled with mineral oil, the second was filled with natural ester and the third was filled with palm oil. The PD generated by the air-filled voids in the insulating papers and pressboards of these transformers with five different conditions were investigated, i.e., non-impregnated paper, impregnated paper for 3 hours, 6 hours, 9 hours and 12 hours. The impregnation process was done with 65◦C liquid temperature, and the pressure in the oven was around 5 mbar. From the experimental results, it can be concluded that the electromagnetic PD transients radiated from the corona discharge of both high-voltage (HV) and low-voltage sides in the air are in the VHF range, and surface discharge frequency is extended up to the UHF range. For the PD in the insulating liquid, the phase resolved PD (PRPD) pattern in the HF range is a valuable tool to characterize the PD sources. The PD in an air-filled void inside the insulating paper of the mineral oil transformer is obviously different compared with those of the natural ester transformer and the palm oil transformer. For the manufacturing of distribution transformers in this research, it is found that after the paper insulation is dried out, the impregnation process for a period of 9 hours is suitable for improving the oil–paper insulation with an acceptable PD level. This paper is the cross-field application by applying the antenna and communication theory for detecting the discharge problems in HV equipment.
Keywords: Antenna; Capacitive sensor; Distribution transformer; Electromagnetic transients; Partial discharge